Successful treatment with Korean herbal medicine and lifestyle management in an obese woman with polycystic ovarian syndrome - Ji Hyeon Lee; Junyoung Jo (Integrative Medicine Research)
In Korea, herbal remedies have been widely used to treat polycystic ovarian syndrome (PCOS). We report the case of a woman with obese-type PCOS who was successfully treated with Korean herbal medicine (KHM) and lifestyle management. A 23-year-old female patient was first examined at our clinic in April 2015. She had amenorrhea for the previous 9 months and presented with obesity and abnormal reproductive hormone levels. She was treated using KHM and lifestyle management. We observed her menstrual cycles and re-evaluated her hormonal levels during the treatment. After KHM therapy, her body weight decreased from 88.2 kg to 66.7 kg. Her menstrual cycles resumed regularly, and the serum levels of the hormones had normalized. No adverse effects on liver and renal functions were observed. This study indicates that KHM might be considered an option for treating women with obese-type PCOS. Further large-scale trials are needed.